The 22 February 2018 landslide mechanism in Pasir Panjang Village, Brebes Regency, Central Java, Indonesia - Wahyu Wilopo; Adam Raka Ekasara; Hendy Setiawan; Dwikorita Karnawati (Geological Engineering Department Universitas Gadjah Mada, 2020)
On 22 February 2018 landslide occurred in Pasir Panjang Village, Salem District, Brebes Regency of Central Java Province, Indonesia. About 8 people were died, 4 people were injured and several infrastructures were damaged due to this landslide. This research is carried out to understand geological-geotechnical condition and to study the initiation mechanism of the landslide. Field investigation and UAV mapping are carried out to detect slip surface and define slope geometry. The rainfall-induced pore-water pressure is estimated by using the Slope Infiltration Distributed Equilibrium (SLIDE) model. Then, limit equilibrium method is used to estimate the safety factor of the slope, while the shear strength parameters are determined by applying back analysis approach that compared with data from laboratory tests. The results show that landslide occurred in permeable layer of silty sand overlaid above impermeable andesitic breccia. Results from back analysis indicate that the shear strength parameters and rainfall intensity are strongly influence the stability of slope against landslide.